New formalism for characterization of simple non-reciprocal networks free from singularity-point problem. (June 2021) - Hasar, Ugur Cem; Kaya, Yunus; Ozturk, Gokhan; Ozturk, Hamdullah; Izginli, Mucahit; Ertugrul, Mehmet
Abstract: A method has been proposed for accurate characterization of non-reciprocal networks without enforcing the passivity principle. Thanks to the introduced different even and odd coefficients, our method has no singularity-point problem as compared with the conventional method. The proposed method is validated by scattering parameter measurements of a ferrite-loaded waveguide shifter. In addition, it is demonstrated by measurements that our method, as compared with the conventional one, is more resistant to random noise due to post-calibration effects. Highlights: A new formalism is proposed based on different even and odd coefficients. Propagation constant retrieval of non-reciprocal networks without passivity principle. Singularity-point-free electromagnetic characterization of non-reciprocal networks.